2019
DOI: 10.1021/acs.chemmater.9b03906
|View full text |Cite
|
Sign up to set email alerts
|

Toward Room-Temperature Thermochromism of VO2 by Nb Doping: Magnetic Investigations

Abstract: Using a synthesis route based on carbon as the reducing agent mixed with Nb-doped V 2 O 5 nanopowders, highly crystallized Nb-doped VO 2 (M) particles, with tunable content of niobium (Nb), are successfully prepared. The morphology and the crystalline structure are first studied in regard to synthesis parameters and chemical composition for various thermal treatment temperatures/durations and niobium doping concentrations. The second part of this paper is devoted to the control, in Nb-doped VO 2 , of the phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 41 publications
(95 reference statements)
1
27
0
Order By: Relevance
“…Vanadium dioxide (VO 2 ) is a well-known thermochromic material, which undergoes a fully reversible first-order metal–insulator transition (MIT) from a low-temperature monoclinic M1 phase ( P 2 1 / c ) to a high-temperature tetragonal phase ( P 4 2 / mnm ) at around 68 °C. At the structural transition, significant changes in atomic organization are intertwined with changes in the electrical, optical, and magnetic properties, , making VO 2 a promising candidate for switching applications, , but with controversies remaining about the Peierls or Mott origin for the phase transition. In our own previous studies, considering that the phase transition is well linked to structural origin, geometrical calculations in agreement with experimental studies suggested that the VO 2 phase transition is a consequence of very short atomic shifts mainly associated with a decrease in the level of second-sphere Coulombic interactions . For practical use, various transition temperatures of VO 2 are desired to fulfill the different demands depending on the applications.…”
mentioning
confidence: 67%
“…Vanadium dioxide (VO 2 ) is a well-known thermochromic material, which undergoes a fully reversible first-order metal–insulator transition (MIT) from a low-temperature monoclinic M1 phase ( P 2 1 / c ) to a high-temperature tetragonal phase ( P 4 2 / mnm ) at around 68 °C. At the structural transition, significant changes in atomic organization are intertwined with changes in the electrical, optical, and magnetic properties, , making VO 2 a promising candidate for switching applications, , but with controversies remaining about the Peierls or Mott origin for the phase transition. In our own previous studies, considering that the phase transition is well linked to structural origin, geometrical calculations in agreement with experimental studies suggested that the VO 2 phase transition is a consequence of very short atomic shifts mainly associated with a decrease in the level of second-sphere Coulombic interactions . For practical use, various transition temperatures of VO 2 are desired to fulfill the different demands depending on the applications.…”
mentioning
confidence: 67%
“…As mentioned above, the metal-insulator transition of VO2 occurred at 68 °C which is too high for room temperature applications. One way to reduce the transition temperature is to substitute V 4+ ions by metal ions with higher valence such as W 6+ , Nb 5+ , Mo 6+ [12,13,14,15]. Among them, W has been considered as one of the most effective ion, lowering the transition temperature (Tc) by 24 °C per 1 at.% [12] while 7.5 °C per 1 at.% and approximatively 8 °C per 1 at.% have been reported for Nb [13] and Mo [16], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Doping has been reported to be effective for this purpose [3] . Various elements such as H and W have been theoretically proposed, as well as experimentally verified, to lower the transition temperature of VO 2 [34,35,70–79] . It is also known that continuous VO 2 films have a low T lum and Δ T sol ; [3,18] therefore, various synthetic and fabrication methods, under optimal thickness, have been developed to improve the thermochromic performance of these films [80–90] .…”
Section: Thermochromic Smart Windowsmentioning
confidence: 99%